HUKUM WARIS ISLAM KONTEMPORER (PERSPEKTIF HERMENEUTIKA MUHAMMAD SYAHRÛR) - Syaekh, Khaerul Ardhian (An Nawawi, 2021)
Muhammad Syahrûr is one of the contemporary Muslim intellectuals who offers a new methodology for interpreting, understanding and establishing the laws in the Qur'an. With this methodology, a rational, systematic, and comprehensive al-Qur'an can become the salih li kulli al-Qur'an of the time of wa eating. This methodology can be used as an effort to have a dialogue with the Qur'an in answering current problems and being able to accommodate changes and developments of the times. Muhammad Syahrûr did a rereading of the Qur'an with a hermeneutic approach based on a linguistic approach which he called manhaj al-tarikh. The use of the linguistic approach by Syahrûr as the method of the Qur'an cannot be separated from his assumption that the Qur'an has two miraculous sides, namely literary and scientific. The first is understood with a descriptive-significant approach while the second with a historical-scientific approach, both of which lie within the framework of linguistic studies. In terms of inheritance law, Muhammad Syahrûr is of the opinion why in the opinion of commentators, men always get double the share of women, and this is considered an axiom as evidenced by the argument that women lack reason and religion.